Tanning Process Restoration and Simulated Sample Development of Ancient Leather - Haoyue LI; Hui WANG; Yue YU; Hailiang YANG; Yang ZHOU; Rulin YANG; Yanan WANG (Pige Kexue Yu Gongcheng, 2024)
The restoration of ancient tanning process and the preparation of ancient leather simulated samples are of great importance to the investigation of deterioration mechanism of leather cultural relics. Natural materials derived from animals, plants and minerals were used for leather processing. Ancient tanning processes including aluminum tanning, iron tanning, vegetable tanning, smoke tanning, mirabilite-flour tanning and oil tanning were restored, and six types of ancient leather simulated samples were obtained. The morphology, thermal stability, physical and organoleptic properties of the leather samples were analyzed. Vegetable tanned leather and iron tanned leather showed well fiber dispersion, high thermal stability as well as soft and full handle. The tanning effects of the other tanning processes were relatively weak, resulting in stiff and thin leathers. However, the appearance, handle and mechanical strengths of all the ancient leather simulated samples were similar with those of modern leather. The results prove the feasibility of the restored ancient tanning process, which provides reliable raw materials for the study of deterioration mechanism of leather cultural relics.